AKREDITASI PERGURUAN TINGGI DAN BUDAYA BUKTI (CULTURE OF EVIDENCE) - Heriteluna, Marselinus (SEPAKAT-Jurnal Pastoral Kateketik, 2017)
Higher Education (PT) as a higher education institution that organizesthe educational process, to produce quality graduates, according to theNational Education goal to educate the Life of the Nation, to implement theTri Dharma Perguruan Tinggi. One of the standards that have to run a PTis the accreditation, to prove that PT has the standards expected in public.Accreditation itself in practice shortly otherwise require supporting data /evidence base as part of the evidence before the attainment of di-approvedby the assessor. This paper attempts to explore Evidence Accreditation andCulture (culture of evidence) as a culture in PT to improve its quality as alearning organization.